Impact of Real-Time Data, Market Sentiment, and Economic Factors on Investment Profitability in Indonesia - Rosy Armaini; Kartika Rachma Sari; Yevi Dwitayanti (The Es Accounting And Finance, 2023)
The study investigates the complex interplay of real-time data, market sentiment, and economic factors in shaping investment profitability in the context of Indonesia. Real-time data, including stock prices and trading volumes, market sentiment derived from sentiment analysis and expert interviews, and economic factors such as GDP growth, inflation rates, and interest rates are examined for their impact on investment outcomes. Quantitative methods, including correlation analysis, regression analysis, and time series analysis, are employed to analyze a comprehensive dataset spanning an extended period. The findings reveal that real-time data has a significant positive influence on investment profitability, underlining the importance of timely access to financial information. Market sentiment also exerts a notable impact, as more positive sentiment correlates with higher profitability. However, the relationship between economic factors and profitability is nuanced, with GDP growth exhibiting a positive influence and inflation rates and interest rates demonstrating weak negative effects. These results offer practical insights for investors and financial analysts, emphasizing the need to consider a holistic approach that incorporates real-time data, sentiment analysis, and macroeconomic indicators in investment decision-making. The study contributes to a deeper understanding of investment dynamics in the emerging market of Indonesia.